Pathways to capacity building - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Participation in agricultural policy making means learning new skills in analysis and organisation: capacity building in short. We look at some of the options.Just where should you start, when you decide to build up your capacities? Well, the fact...